Pengaruh Perputaran Piutang Dan Penjualan Terhadap Laba Bersih Pada Perusahaan Manufaktur - Masta Sembiring (LPPM POLITEKNIK LP3I BANDUNG, 2022)
The problem in this study is that in an effort to achieve high profits, the company must be able to earn as much income as possible, one of which is by increasing sales and obtaining receivables income. good by the company shows that the receivables turnover is running efficiently. Whether the movement of receivables turnover can affect profit and whether sales can affect profit, and whether the movement between receivables and sales turnover can affect the movement of net income. The purpose of this study was to determine whether receivables turnover had an effect on profit and whether sales also had an effect on profit. And, whether receivables turnover and sales together have an effect on profits in food sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020. The results showed that the effect of accounts receivable turnover on net income partially there was a significant influence of receivables turnover on net income. With the increase in receivables turnover, it is followed by an increase in net profit for food companies listed on the Indonesia Stock Exchange with a 95% confidence level. And the influence of sales on net income shows that partially there is a significant effect of sales on net income. With the increase in sales, it is followed by an increase in net profit for food companies listed on the Indonesia Stock Exchange with a 95% confidence level. As well as receivables and sales turnover together have a significant effect on the net profit of Food companies listed on the Indonesia Stock Exchange in 2017-2020.